Catatan Akademik Atas Tren “Social-Tech” Dalam Penelitian Psikologi Siswa Pada Olimpiade Penelitian Siswa Indonesia (OPSI) - Arlinkasari, Fitri; Yudhaningrum, Lupi; Maulana, Herdiyan (ANIMA Indonesian Psychological Journal, 2026)
The "Social-Tech" approach is gaining popularity in student Psychology research, as evidenced by the Olimpiade Penelitian Siswa Indonesia (OPSI). Beyond being a research theme, a growing number of students are also implementing the use of technology in their research, but without a solid theoretical understanding and structured guidance and mentoring. In this Letter to the Editor (LtE), the authors urge psychology practitioners and scientists, as well as journal managers, to move from access to action, as it is a shared responsibility to ensure that innovation thrives on a solid foundation of psychology theory, sound methodology, and strong research ethics.